Characteristics and management of primary and other immune thrombocytopenias: Spanish registry study. Issue 8 (14th September 2017) - Palau, Javier; Sancho, Esther; Herrera, Magdalena; Sánchez, Sol; Mingot, María Eva; Upegui, Rosa Isabel; Rodríguez Salazar, Mª José; de la Cruz, Fátima; Fernández, Mª Cristina; González López, Tomás José; Hernández, José Julio; Ríos, Eduardo; et al.
ABSTRACT: Background: The natural history and its modulation by treatments administered for immune thrombocytopenia (ITP) in the clinical practice remains unknown. In addition, little information is available on the characteristics and management of ITP in Spain. Methods: We conducted an observational, multicenter, registry in 70 Hematology Services from Spain between 2009 and 2011, which included children from 2 months of age and adults with primary ITP or another ITP diagnosed within the last 6 months (platelet count [PC] < 100 × 10 9 /l). Patients were followed-up at 6 and 12 months. Results: 484 patients were included (median [Q1, Q3] age 52 [29, 74] years, 87.6% adults), 56% women, 10.5% with secondary ITP. Median (Q1, Q3) PC at diagnosis was 12 × 10 9 /l (4, 32); 72% of patients had bleeding symptoms (62% cutaneous bleeding, 29% oral cavity bleeding, 18% epistaxis). 81% of patients with primary ITP received first-line treatment, mainly with corticosteroids (>6 weeks in 59% of cases), either alone (41%) or associated with intravenous immunoglobulin (33%). The response (≥30 × 10 9 /L) to first-line treatment was 92%. A total of 19% of patients received second-line treatment and 6% additional treatments. At 12 months, 74% of primary ITP patients maintained a PC ≥ 100 × 10 9 /L in absence of treatment (10% still had hemorrhagic manifestations). Conclusions: Characteristics of Spanish ITP patients are comparable to those from other countries. Although a high response rate to first-line treatments is observed, at 1 year, the disease persists in around one quarter of patients. Overall therapeutic management in Spain conforms to current recommendations, except for an excessive duration of corticosteroids therapy.